Environmental Tobacco Smoke in Occupational Settings - Vital, Nádia (2021)
Funding: This work was funded by the Portuguese institutions Fundação Calouste Gulbenkian, Administração Central do Sistema de Saúde (ACSS) and FCT/MCTES through funding to ToxOmics (UIDB/00009/2020; UIDP/00009/2020).